Teaching and learning with instructional humor: a review of five-decades research and further direction - Zhou, Weichen; Lee, Jun Choi (Frontiers in Psychology, 2025)
The discussion about how to use instructional humor in class to promote teaching and learning efficiency has always been a concern of researchers in recent decades. The present project summarizes extant studies on instructional humor and provides a detailed review of research findings. First, the definition and classification of instructional humor are overviewed. Then, the study introduces three theoretical frameworks, namely Instructional Humor Processing Theory (IHPT) and other two alternative models, which, respectively, based on Self-Determination Theory (SDT) or from an integrative perspective of cognition and affection, explaining how humor works in education settings. Based on the theoretical clarification of instructional humor, the paper further reviews existing empirical evidence regarding teachers’ use of humor in class and its impact on students’ learning, with emphasis on explaining inconsistencies in previous conclusions and identifying limitations in extant relevant works. The detailed analysis and comparison of previous results regarding instructional humor offer potential directions for further relevant research. Finally, the study concludes with feasible advice for teachers to maximize the positive benefits of humor in class.